2020
DOI: 10.1186/s12911-020-1089-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of data quality rules in administrative health data using association rule mining

Abstract: Background: Data quality assessment presents a challenge for research using coded administrative health data. The objective of this study is to develop and validate a set of coding association rules for coded diagnostic data. Methods: We used the Canadian re-abstracted hospital discharge abstract data coded in International Classification of Disease, 10th revision (ICD-10) codes. Association rule mining was conducted on the re-abstracted data in four age groups (0-4, 20-44, 45-64; ≥ 65) to extract ICD-10 codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…While patient record review has been suggested as the best method to derive multimorbidity prevalence as it is not reliant on coding and data entry [ 15 , 16 ], large studies lack access to individual patient notes or direct accounts of patients’ conditions. Errors in coding subsequently implicate the accuracy of research using data from large databases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While patient record review has been suggested as the best method to derive multimorbidity prevalence as it is not reliant on coding and data entry [ 15 , 16 ], large studies lack access to individual patient notes or direct accounts of patients’ conditions. Errors in coding subsequently implicate the accuracy of research using data from large databases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to smaller databases, standards of governance are generally required to ensure diagnoses are reliably coded in large datasets. Some challenges in using larger databases include the accuracy of the coding system used, and the reliability of coding as hospital records may be coded by non-physicians and may not reflect the actual codes from the physicians' perspectives [14,15]. This is confounded by the impracticability to go through individual patient notes or obtain a direct account of the patient's conditions.…”
Section: Introductionmentioning
confidence: 99%
“…14 Data quality rules can be used to assess coded data and allow comparisons across institutions and countries. 15 Reporting of methods used for data pre-processing and data linkage. This includes the methods used to assess the quality of linkage and the results of any data pre-processing and linkage (with provision of false positive and false negative rates, comparisons of linked and unlinked data, and any sensitivity analyses).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, they tried to analyze the rules and compare them with the physician's decisions. (Peng et al, 2020) used association rules in a hospital discharge abstract data in order to investigate whether the coding system in the case study hospital could be improved or not. Results showed that the rules extracted could de ne different codes and helped the coding system to be more structured.…”
Section: Literature Reviewmentioning
confidence: 99%